Peran ASEAN Outlook on the Indo-Pacific Sebagai Strategi Kebijakan Luar Negeri Indonesia Di Kawasan Indo-Pasifik - Ely Nurmawati; Chandra Purnama; Wawan Budi Darmawan (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2022)
The purposes of this paper is to see the role of the ASEAN Outlook on the Indo-Pacific as Indonesia's foreign policy strategy in context to responding the dynamics that occur in the region. Nowadays, competition between global actors is getting stronger and creates new, more complex tensions. One of them is marked by the increasing impact of the rivalry that occurs between the United States and China in the Indo-Pacific region. Indonesia, with its strategic position, take advantage of ASEAN as a medium to achieve its interests through a soft power approach. This paper uses the concepts of foreign policy in perspective strategy and rivalry interstate with a descriptive qualitative research approach. The results of the study describe the process from the creation and the importance of the ASEAN Outlook on the Indo-Pacific for countries in the region.